IDENTIFIKASI DIVERSITAS MIKROBA PADA PANGAN ROTI EXPIRED DAN NON-EXPIRED - Ira Rahmawati; Labibah Fatihatu hanin; Muhimatul Ummami (Program Studi Biologi, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas PGRI Banyuwangi, Jalan Ikan Tongkol No 01, Telp (0333) 421593, 428592 Banyuwangi 68416, 2025)
This study aims to identify microbial biodiversity in bread that has not passed its expiration date (non-expired) and that has passed its expiration date (expired). The research methods include microbial isolation, colony morphology identification, Gram staining, biochemical tests (sugar, catalase, motility, and oxidative-fermentative tests), and diversity analysis using the Shannon-Wiener index. The results showed that microbes in expired bread tend to be more varied than non-expired bread, with the number of colonies increasing with the length of the expiration date. Gram staining showed the dominance of Gram-negative bacteria, although Gram-positive bacteria were also found. Biochemical test analysis revealed the dominant glucose fermentation ability in all colonies. Based on the diversity analysis, the highest level of microbial diversity was found in 8-day expired bread with an index of 0.67, while non-expired bread had an index of 0.56. These findings emphasize the importance of paying attention to the expiration date of bread to prevent microbial contamination that is potentially harmful to health.